Second primary chondrosarcoma of the maxilla: a case report - Pabi, Shreeya; Yanthan, Yanpothung; Gupta, Sweety; Das, Biswajyoti; Ibrahim, Ajas; Kassim, Naseef; Varshney, Saurabh; Singh, Divya; Gupta, Manoj (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2020)
We are reporting an uncommon case of second primary chondrosarcoma of the maxilla in a 52-year-old male patient. Patient had first been diagnosed in 2004 with chondrosarcoma of the right maxilla. He had undergone right partial maxillectomy for the same. Since 2016 he had started noticing a swelling over the left side of the maxilla. Repeated biopsies from the growth showed no evidence of any malignancy. Hence, he was kept on routine follow up. However, in 2018, during follow up the growth had increased in size - hard swelling present in remnant post partial maxillectomy cavity, non-tender -and a punch biopsy was taken, revealing a well differentiated chondrosarcoma. A diagnosis of second primary chondrosarcoma of the maxilla was made based on Warren and Gates criteria. A brief discussion on the radiologic and histologic presentation of the tumor and the treatment modalities of this unusual tumor is discussed.